2020
DOI: 10.1007/s00705-020-04741-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of astrovirus in children with gastroenteritis in southwestern Nigeria

Abstract: Human astrovirus (HAstV) is recognized as one of the major causative agents of acute gastroenteritis in children worldwide. Data on the genetic diversity of HAstV in Nigeria are limited. The aim of this study was to determine the prevalence and molecular epidemiology of classical HAstV in children under 5 years of age with acute gastroenteritis in Ogun State, Nigeria. Fecal samples (331) as well as socio-demographic and clinical data were collected across the three senatorial districts of the state from Februa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…This observation is similar to what we have reported previously during 2011 to 2016 at 57.4% in the same geographical area 13 , suggesting that gastroenteritis in children in Thailand are infected with a wide variety of enteric viruses and require more attention on the situation. Nevertheless, high rate of co-infection with other enteric viruses is not uncommon, it has also been reported elsewhere, such as 38.2% in Nigeria 23 and 71% in Germany 34 . As expected and shown in Table 1 that the rotavirus was found to be the most common virus that coinfected with HAstV infection since rotavirus is the most common virus that causes gastroenteritis in children worldwide 35,36 .…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This observation is similar to what we have reported previously during 2011 to 2016 at 57.4% in the same geographical area 13 , suggesting that gastroenteritis in children in Thailand are infected with a wide variety of enteric viruses and require more attention on the situation. Nevertheless, high rate of co-infection with other enteric viruses is not uncommon, it has also been reported elsewhere, such as 38.2% in Nigeria 23 and 71% in Germany 34 . As expected and shown in Table 1 that the rotavirus was found to be the most common virus that coinfected with HAstV infection since rotavirus is the most common virus that causes gastroenteritis in children worldwide 35,36 .…”
Section: Discussionmentioning
confidence: 56%
“…For instance, in South America, the prevalence of HAstV infection in Brazil was reported with low infection rate at 0.8% 17 , whereas in North America a prevalence was reported at 3.5% in Mexico 18 . In Africa, a prevalence of HAstV infection was reported at 7.0% in South Africa 19 , 9.9% in Kenya and Gambia 3 , 10.3% in Congo 20 , 11-14% in Egypt 21,22 , and 19.4% in Nigeria 23 . In Europe, a prevalence of HAstV infection was reported at 2.5% in Netherland 24 and 3% in Italy 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, astrovirus prevalence ranges between 2% and 10% with a lower detection rate of novel astrovirus strains [2]. Different studies reporting astrovirus prevalence globally in hospitalized and outpatients demonstrated fluctuating ranges [10][11][12]15,16] with the highest recorded in Nigeria [17].…”
Section: Discussionmentioning
confidence: 99%
“…With an astrovirus-causing acute gastroenteritis’ global average incidence of 11%, the highest prevalence of human astrovirus (HAstV) infections was in the group of children between 37 and 48 months old [ 47 , 48 ]. HAstV infection mainly occurs during the dry season in the African continent; meanwhile, the highest occurrence reported in the tropical areas is often in the rainy season and winter season in temperate climate countries [ 47 , 49 ]. Patients usually manifested with diarrhoea, fever, vomiting, and abdominal pain [ 48 , 50 ].…”
Section: Causative Agents Of Agementioning
confidence: 99%